Answer:
1) C = 3
2) B = 5
3) C = 8
Step-by-step explanation:
Question 1)
We have:
[tex](2x+3)(4x-1)[/tex]
Distribute:
[tex]=(2x+3)(4x)+(2x+3)(-1)[/tex]
Distribute:
[tex]=8x^2+12x-2x-3[/tex]
Combine like terms:
[tex]=8x^2+10x-(3)[/tex]
Therefore, C = 3.
Question 2)
We have:
[tex](x+2) (2x^2+x-1)[/tex]
Distribute:
[tex]\displaystyle =(x+2)(2x^2)+(x+2)(x)+(x+2)( - 1)[/tex]
Distribute:
[tex]=(2x^3+4x^2)+(x^2+2x)+(-x -2)[/tex]
Combine like terms:
[tex]=2x^3+(5)x^2+x-2[/tex]
Therefore, B = 5.
Question 3)
We have:
[tex](x+2)(x^2-3x-2)[/tex]
Distribute:
[tex]=(x+2)(x^2)+(x+2)(-3x)+(x+2)(-2)[/tex]
Distribute:
[tex]=(x^3+2x^2)+(-3x^2-6x)+(-2x-4)[/tex]
Combine like terms:
[tex]=x^3-x^2-(8)x-4[/tex]
So, C = 8.